GM1 and GM2 gangliosides: recent developments - Bisel Blaine (Biomolecular Concepts, 2014)
GM1 and GM2 gangliosides are important components of the cell membrane and play an integral role in cell signaling and metabolism. In this conceptual overview, we discuss recent developments in our understanding of the basic biological functions of GM1 and GM2 and their involvement in several diseases. In addition to a well-established spectrum of disorders known as gangliosidoses, such as Tay-Sachs disease, more and more evidence points at an involvement of GM1 in Alzheimer’s and Parkinson’s diseases. New emerging methodologies spanning from single-molecule imaging in vivo to simulations in silico have complemented standard studies based on ganglioside extraction.